Experimental and theoretical study on microalgae harvesting process by using continuous flow low gradient magnetic separation (lgms) approach - Lim, Ka Yee (2023)

(untitled)
Microalgae are popular choice in pharmaceutical supplements, "healthy foods" aimed at preventing various diseases, such as gastric, ulcers, atherosclerosis, and hypercholesterolemia. Furthermore, in an industrial context, Chlorella vulgaris has been utilized in wastewater treatment (eg. heavy metals removal), eutrophication treatment, carbon dioxide capture and biofuel processing. The microalgae harvesting method selected in our study was low gradient magnetophoretic separation (LGMS) which had the novelty of cost effective and easy maintenance, which remove the microalgae by magnetic fields after attaching microalgae (-ve) to cationic polyelectrolyte PDDA-surface-functionalized iron oxide nanoparticles (SF-IONPs) (+ve). Although this method is fast and efficient, current research gap of LGMS in Microalgae Harvesting were: (1) the operations of LGMS only able to be carried out in batch therefore limited the scale up of LGMS; (2) Premixing has only been done by manual in current technology causing this approach to be labour-intensive and timeconsuming. Therefore, this study aimed to build an automated continuous microalgae harvesting process with a staggered static mixer for scaling up the microalgae harvesting and achieve automated mixing which avoid the manual premixing. This study carried out by 3 steps: (1) The SF-IONPs concentration predetermination between 50 to 200 mg/L within the retention time of 10 minutes by batchwise LGMS Microalgae Harvesting. (2) A Continuous Flow Low Gradient Magnetic Separation approach in Microalgae Harvesting (CF-LGMS-MH) with the pre-determined optimum SF-IONPs concentration and the minimum retention time. This analysis provides an insight of the effect of baffle mixing ranging from (non-baffle, 1.5D, 2.0D, and 2.5D) toward the attachment condition of microalgae cells and the SF-IONPs. (3) COMSOL Multiphysics fluid flow simulation to verify the effect of mixing toward the cells attachment. From our results, the optimum SF-IONPs dosage for CF-LGMS-MH iii was 150 mg/L. whereby, the best separation efficiency of 99.93% was given at the baffle spacing of 1.5D within retention time of 6 minutes which is consistent with simulation results in COMSOL Multiphysics.